Cartel Stability and the Curvature of Market Demand - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1994)
The stability of collusion is analysed for a family of demand functions whose curvature is determined by a parameter varying between zero and infinity. If demand is sufficiently convex, firms may prefer to act as quantity setters in order to increase cartel stability. Otherwise, price-setting behaviour enhances their ability to collude.
Keywords: 330